Measuring Inefficiency of the Czech Labour Market - Daniel Němec (Review of Economic Perspectives, 2015)
This paper aims to quantify the performance of the Czech regional labour markets and to reveal the most influential economic factors standing behind its dynamics in the last fifteen years. Investigated labour markets are described using matching function approach. The successful matches are treated as an output of production process, where the unemployed are paired with vacancies. Efficiency of this matching process plays an important role in determining unemployment outflows. Using stochastic frontier model approach, dynamics of quantified efficiency terms is revealed and differences among regions are evaluated. The model specification includes a fixed effect term, where individual effect terms and inefficiency terms are estimated jointly. The stochastic frontier is estimated using monthly and quarterly regional panel data of 77 districts for the period 1999-2014. Matching efficiency of the Czech regional labour markets is negatively influenced people who have been unemployed for a long time and by the unemployed aged over 50 years. Although all districts were able to operate at their stochastic frontiers of matching, an upward trend in the inefficiency has been found within the investigated period. These tendencies are accompanied by rising disparities among the regions. Low levels of estimated matching inefficiency do not necessary mean the low unemployment in the corresponding districts.
Keywords: 330